1997
DOI: 10.1073/pnas.94.22.12070
|View full text |Cite
|
Sign up to set email alerts
|

Posttranslational regulation of cyclin D1 by retinoic acid: A chemoprevention mechanism

Abstract: The retinoids are reported to reduce incidence of second primary aerodigestive cancers. Mechanisms for this chemoprevention are previously linked to all-trans retinoic acid (RA) signaling growth inhibition at G 1 in carcinogen-exposed immortalized human bronchial epithelial cells. This study investigated how RA suppresses human bronchial epithelial cell growth at the G 1 -S cell cycle transition. RA signaled growth suppression of human bronchial epithelial cells and a decline in cyclin D1 protein but not mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
180
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(191 citation statements)
references
References 33 publications
(38 reference statements)
8
180
2
1
Order By: Relevance
“…Since the levels of the Cdk4-regulating protein Cyclin D1 decline in all cell lines, the drop in Cdk-4 activity may, at least in part, be explained by this event. Based on the fact that RA and other receptor-non-selective and growth-suppressive retinoids enhance proteasomedependent Cyclin D1 degradation, it has been hypothesized that proteolysis of this protein is a common chemoprevention signal, at least in normal and transformed human bronchial epithelial cells (Langenfeld et al, 1997;Boyle et al, 1999). Although we cannot exclude that Cyclin D1 downregulation may equally represent a chemoprevention signal in response to HPR, nevertheless our results point out that unlike RA, HPR suppresses Cyclin D1 expression by a transcriptional rather than posttranslational mechanism, emphasizing further the di erent mode of action of these two retinoids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the levels of the Cdk4-regulating protein Cyclin D1 decline in all cell lines, the drop in Cdk-4 activity may, at least in part, be explained by this event. Based on the fact that RA and other receptor-non-selective and growth-suppressive retinoids enhance proteasomedependent Cyclin D1 degradation, it has been hypothesized that proteolysis of this protein is a common chemoprevention signal, at least in normal and transformed human bronchial epithelial cells (Langenfeld et al, 1997;Boyle et al, 1999). Although we cannot exclude that Cyclin D1 downregulation may equally represent a chemoprevention signal in response to HPR, nevertheless our results point out that unlike RA, HPR suppresses Cyclin D1 expression by a transcriptional rather than posttranslational mechanism, emphasizing further the di erent mode of action of these two retinoids.…”
Section: Discussionmentioning
confidence: 99%
“…Signi®cantly, however, Cyclin D1 protein levels markedly decreased in all three cell lines after retinoid treatment (Figure 6), a ®nding that may explain the drop in Cdk4 function given that its activity depends on Cyclin D1. Since RA and other retinoids induce proteasome-mediated Cyclin D1 degradation, and this may represent an e ective growth suppressing and cancer chemoprevention signal (Langenfeld et al, 1997;Boyle et al, 1999), we determined whether a similar mechanism accounted for the downregulation of Cyclin D1 by HPR. For this purpose, cells were pre-treated with a non-toxic dose of calpain inhibitor I (the inhibitor of the 26S proteasome pathway) prior to treatment with HPR.…”
Section: Regulation Of Cdks Activity By Hprmentioning
confidence: 99%
See 1 more Smart Citation
“…Downregulation of cyclin D1 with the GG genotype in these lesions with a regimen based on the bexarotene relative 13-cis-retinoic acid (13cRA) was associated with cancer prevention (14, 15); the regimen did not downregulate overexpression of cyclin D1 with the AG or AA genotype [the A allele preferentially produces an altered transcript that resists retinoic acid degradation; ref. (16)] or prevent cancer in patients with such lesions. The prevalence of the GG genotype in cyclin D1 overexpression seems to be about 30%.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that mTOR/PI3 kinase regulated p70S6 kinase-dependent control and/or PI3 kinase/eIF4E-mediated control may participate in cyclin D1 translational control. [32][33][34][35][36] In addition, a study from human sarcoma cell lines has suggested that overexpression of cyclin D1 protein may result from enhanced protein stability due to an altered ubiquitin/proteasome pathway involved in the degradation of cyclin D1 protein. 37 Therefore, it is possible that translational/post-translational regulation of cyclin D1 protein may provide a timing fashion for control of rapid cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%